Développement d’un modèle statistique de prédiction de la durée de vie du rachis lombaire, dépendant de la contrainte appliquée, de l’âge et de la densité osseuse - Houcine Ayari; Marc Thomas; Sylvie Doré (Perspectives Interdisciplinaires sur le Travail et la Santé)
Due to vertebral densimetric and structural inhomogeneity between individuals and the fact that bone strength varies with bone density and discontinuities within the trabecular lattice which changes with age, vertebral fatigue behavior cannot be considered as depending only on the cyclic stress. In this study, a lifetime prediction model is proposed for evaluating the number of cycles before damage as a function of the cyclic stress, bone density and age of the specimen. Due to their large dispersion, the results of the fatigue tests published by Brinckmann (1988) have been classified for analysis using the experiment design method. A nonlinear model presenting a coefficient of determination R2 of 94 % has been established. By comparing the values predicted by this model with the results of the fatigue tests conducted by Hansson (1987), a certain consistency can be noticed in the results. This study justifies the assumption that bone density and age in addition to cyclic stress have an effect on the fatigue of the rachis.